LEGAL POLICY ANALYSIS ON THE GRANTING OF REMISSIONS FOR PRISONERS IN CLASS IIB PRABUMULIH PRISON - Misbah Ayu Nafarizka; Mulyadi Tanzili; Darmadi Djufri (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study analyzes the implementation of remission policies at the Class IIB Detention Center in Prabumulih and evaluates their alignment with Indonesia’s correctional goals of rehabilitation and social reintegration. It also examines the challenges encountered in the remission process, including overcrowding, inconsistent monitoring of rehabilitation programs, and concerns about fairness, particularly for serious offenders. Using a qualitative empirical approach, the research combines legal analysis with in-depth interviews involving prison officials, inmates, and legal experts, as well as documentation of remission data. The findings show that, in general, inmates who receive remission have fulfilled the required legal criteria. Remission is granted in two forms: general remission, typically provided during national and religious holidays, and special remission, which is given to inmates demonstrating significant rehabilitative progress. However, the effectiveness of the policy is constrained by several factors, including overcrowded conditions and inconsistent supervision of inmate development programs. In addition, public perceptions of fairness, especially regarding remission for serious offenders, pose challenges to the credibility of the system. These issues highlight the need for greater transparency and consistency in policy implementation. In conclusion, while remission policies contribute to the correctional objectives of rehabilitation and reintegration, improvements are necessary. Strengthening access to rehabilitation programs, enhancing monitoring mechanisms, and increasing public awareness about the purpose of remission are recommended to ensure a more effective, fair, and accountable system. Keywords: Remission; Correctional System; Rehabilitation